Variations In The Substitution Of Peanut Flour For Almond Flour On Macaron Skin Characteristics - Ida Ningrumsari (Jurnal Multidisiplin Sahombu, 2024)
Macarons are simple cakes usually made from egg whites, sugar and almond flour. Almonds and almond flour are not produced in Indonesia, and have to be imported from abroad, causing the price of almonds and almond flour to be quite expensive on the market. Therefore, in this research, peanut flour was substituted for almond flour in making macarons. The aim of this research is to find the right substitution for peanut flour for almond flour to produce the best macaron skin characteristics in terms of water content, protein content, fat content, swelling power and organoleptics. This research used a Randomized Group Design (RAK) consisting of 6 treatments and 4 repetitions. The treatment was the substitution of 0%, 10%, 20%, 30%, 40% and 50% peanut flour for almond flour at 100%, 90%, 80%, 70%, 60% and 50%. The analysis in this research includes water content, protein content, fat content and swelling power as well as organoleptic tests in the form of color, aroma, taste, texture and appearance of the macarons produced. The results showed that treatment D (30:70) produced the best macaron characteristics. This determination was based on the level of preference for aroma 4.25 (like), texture 4.30 (like), and taste 4.41 (like). The nutritional content of treatment D (30:70) consists of water content of (2.89%), protein content of (5.16%) and fat content of (18.54%) and flowering capacity of (30.02%).